NTRK Fusions and TRK Inhibitors: Potential Targeted Therapies for Adult Glioblastoma - Wang, Yuekun; Long, Piaopiao; Wang, Yu; Ma, Wenbin (Frontiers in Oncology, 2020)
Introduction: Glioblastoma multiforme (GBM) is the most common primary central nervous (CNS) system malignancy with a poor prognosis. The standard treatment for GBM is neurosurgical resection, followed by radiochemotherapy and adjuvant temozolomide chemotherapy. Predictive biomarkers, such as methylation of the promoter region of the O6-methylguanine DNA methyltransferase (MGMT) gene, can successfully distinguish subgroups with different prognosis after temozolomide chemotherapy. Based on multiomics studies, epidermal growth factor receptor (EGFR), vascular endothelial growth factor (VEGFR), BRAF V600E mutation, neurotrophic tyrosine receptor kinase (NTRK) fusions and other potential therapy targets have been found. Methods: We have reviewed the preclinical and clinical evidence for NTRK fusions and TRK inhibitors therapy in cancers with NTRK fusions in pan-cancer and gliomas. Results: Several NTRK1/2/3 fusions have been reported in GBM and preclinical studies have proven that NTRK fusions are potential driver mutations in some high-grade gliomas. Tropomyosin receptor kinase (TRK) inhibitors have shown efficacy as targeted therapies for extracranial tumors with NTRK fusions in recent clinical trials, with potential CNS tolerability and activity. However, whether NTRK gene fusions can affect survival status, the efficacy and resistance of TRK inhibitors in GBMs are lacking high-level evidences. Conclusions: For GBM patients, NTRK fusions and TRK inhibitors are potential target therapy strategy but remain biological mechanism and clinical significance unclarified. More clinical data and future clinical trials are needed to provide more evidence that supports targeted therapy for GBM with NTRK fusions.